Best Operational and Maintenance Practices for City Bus Fleets to Maximize Fuel Economy - World Bank (Washington, DC, 2014)
In most large cities in developing countries, buses continue to be the public transport option of choice, carrying a large share of urban travelers. However, transit bus companies in these countries are often cash-strapped. In many cases, the operating cost per bus kilometer exceeds revenues and bus fares are often kept low irrespective of the cost of providing service. Many cities are dominated by old and fuel-intensive buses with high operating costs. Transit systems are also often plagued by overcrowded and undependable service, congested roadways and chaotic operating environments. Across the board, city officials in developing countries are under strong pressure to improve the efficiency and enhance the attractiveness of bus transportation. Fuel makes up a relatively large fraction of total bus operating costs, especially when labor costs are low, as in many developing countries. Fuel costs can be reduced by improving the driving style of bus drivers and through sound maintenance practices. A safe and economical driving style can reduce variable costs, decrease down time due to repair work and maintenance, mitigate negative environmental impacts and improve road safety. Similarly, well-maintained buses that are properly tuned and adjusted tend to be cleaner, safer and consume less fuel than poorly maintained vehicles. This guidance note provides detailed and practical recommendations on how city bus operations managers and their technical staff can plan and implement such enhancements to their fleets through Operations and Maintenance (O&M) practices without significant capital investments. By implementing such recommendations, municipal officials and bus operators can increase the efficiency and fuel economy of their bus systems and reduce their cities' energy consumption, congestion and pollution.